The role of metabolism on regulatory T cell development and its impact in tumor and transplantation immunity - Bulygin, Aleksey S.; Khantakova, Julia N.; Shkaruba, Nadezhda S.; Shiku, Hiroshi; Sennikov, Sergey S. (Frontiers in Immunology, 2022)
Regulatory CD4+ T (Treg) cells play a key role in the induction of immune tolerance and in the prevention of autoimmune diseases. Treg cells are defined by the expression of transcription factor FOXP3, which ensures proliferation and induction of the suppressor activity of this cell population. In a tumor microenvironment, after transplantation or during autoimmune diseases, Treg cells can respond to various signals from their environment and this property ensures their suppressor function. Recent studies showed that a metabolic signaling pathway of Treg cells are essential in the control of Treg cell proliferation processes. This review presents the latest research highlights on how the influence of extracellular factors (e.g. nutrients, vitamins and metabolites) as well as intracellular metabolic signaling pathways regulate tissue specificity of Treg cells and heterogeneity of this cell population. Understanding the metabolic regulation of Treg cells should provide new insights into immune homeostasis and disorders along with important therapeutic implications for autoimmune diseases, cancer and other immune-system–mediated disorders.